The Tissue Architecture of Oral Squamous Cell Carcinoma Visualized by Staining Patterns of Wheat Germ Agglutinin and Structural Proteins Using Confocal Microscopy - Silveyra, Estefanía (2021)
Abstract: Objectives: Tissue architecture and cell morphology suffer profound alterations during oral cancer and are important markers for its progression and outcome. For precise visualization of tissue architecture in oral cancer, we used confocal microscopy to examine the staining pattern of wheat germ agglutinin, a lectin that binds membrane glycoproteins, and the staining patterns of structural proteins. Materials and Methods: Paraffin sections of oral squamous cell carcinoma were stained with fluorescently labeled wheat germ agglutinin and with antibodies against structural proteins, which were revealed by immunohistochemistry with tyramide signal amplification. Results: Membrane localization of wheat germ agglutinin was markedly decreased in the basal layers and in regions of tumor invasion, accompanied by cytoplasmic redistribution of E-cadherin, -actin and syndecan-1. Wheat germ agglutinin staining clearly identified tumor clusters within the surrounding stroma, and tumor cells with elongated morphology. Conclusions: Our results suggest that the wheat germ agglutinin staining pattern is indicative of the degree of cell cohesion in oral squamous cell carcinoma, which decreases in basal layers and invasive tumor clusters with more migratory morphologies. Wheat germ agglutinin staining in combination with confocal microscopy could constitute, therefore, a valuable tool for the study of tissue architecture in oral cancer.